EFFECT OF SEED PRIMING ON GERMINATION AND SEEDLING GROWTH OF SORGHUM (Sorghum bicolor (L. MOENCH) - Lawal, A.A.; Mangshin, G.B.; Shuaibu, Y.M.; Kuwre, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Seed emergence and germination are critical initial phases in the plant life cycle, during which the embryo successfully overcome dormancy, activate metabolic process, and stimulate early seedling establishment. Seed priming is a simple, low-cost pre-sowing technique used to enhance germination performance and early seedling vigor. The present study was carried out to investigate the effects of plant priming agents on germination, and seedling growth responses of sorghum seeds. The treatments consisted of soaking the seeds of sorghum in moringa leaf extract, aloe vera extract, coconut water extract, lemon grass and lime extract for 10hours. The result reveals that, priming with moringa leaf extract, aloe vera extract, coconut water extract and lemon grass increased final germination percentage, germination index, root length, shoot length and seedling fresh weight of both cultivars as compared to all pre sowing seed treatments including control. Seeds of sorghum cultivars primed with moringa leaf extract, aloe vera extract, coconut water extract and lemon grass, significantly reduced the time taken to 50% emergence and mean emergence, increased final seedling emergence percentage and seedling growth. Results also indicated that priming with varying plant aqueous extract improved germination potential and seedling establishment of the cultivars and it proved to be better option than control which resulted in poor emergence and seedling growth. The highest germination was recorded on seeds primed with moringa leaf extract with (93.33%) and is recommended for priming of sorghum seed.